2020
DOI: 10.2131/jts.45.795
|View full text |Cite
|
Sign up to set email alerts
|

Cell density-dependent accumulation of low polarity gold nanocluster in cultured vascular endothelial cells

Abstract: We have previously reported the cytotoxicity and various biological responses of organic-inorganic hybrid molecules. However, because all the molecules used were electrophilic, the effect of the hybrid molecule without electrophilicity remains unclear. The glutathione-protected gold nanocluster, Au 25 (SG) 18 , is an organic-inorganic hybrid molecule that shows a low intramolecular polarity and high stability. In this study, we examined the cytotoxicity and intracellular accumulation of Au 25 (SG) 18 in cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Studies of aquatic organisms show nanoparticles accumulate in fish tissues (liver, intestine, gill, and muscles), urchin embryos, and algae [ 173 , 174 , 175 , 176 , 177 ]. Similarly, in human, animal, and cell line studies, nanoparticles were shown to accumulate in the cells of the brain, kidneys, liver, spleen, heart, and lungs [ 178 , 179 , 180 , 181 ]. Once nanoparticles accumulate in cells, they can cause apoptosis, histological changes, necrosis, lysis, atrophy, and DNA damage…”
Section: Factors Affecting Toxicitymentioning
confidence: 99%
“…Studies of aquatic organisms show nanoparticles accumulate in fish tissues (liver, intestine, gill, and muscles), urchin embryos, and algae [ 173 , 174 , 175 , 176 , 177 ]. Similarly, in human, animal, and cell line studies, nanoparticles were shown to accumulate in the cells of the brain, kidneys, liver, spleen, heart, and lungs [ 178 , 179 , 180 , 181 ]. Once nanoparticles accumulate in cells, they can cause apoptosis, histological changes, necrosis, lysis, atrophy, and DNA damage…”
Section: Factors Affecting Toxicitymentioning
confidence: 99%
“…Briefly, confluent vascular endothelial cells, vascular smooth muscle cells, fibroblastic IMR-90 cells, and epithelial LLC-PK1 cells grown in 24-well culture plates were treated with DPDTe, DPDSe, and DPDS for 24 h. After incubation, a portion of the treated medium was collected, and LDH activity was measured, as a marker for cell death, using the CytoTox 96 Non-Radioactive Cytotoxicity Assay kit. To analyze cell viability, mitochondrial activity was measured using a previously reported method with modification [22]. Confluent vascular endothelial cells grown in 24-well culture plates were treated with organotellurium compounds for 24 h. The conditioned media were discarded, and DMEM-AlamarBlue (10:1) solution was added to each well, and the cells were further incubated for 2 h. After incubation, DMEM-AlamarBlue was transferred from each well to a black bottom 96-well plate and fluorescence was measured (Ex = 544 nm, Em = 590 nm) using a multimodal plate reader (BMG LABTECH, Ortenberg, Germany).…”
Section: Cytotoxicity Assay and Cell Viability Assaymentioning
confidence: 99%